Perinatal management of twin pregnancy discordant for intrapericardial teratoma: A case report and literature review - Gil-Pugliese, Savino (2024)
This publication aims to provide an overview of the clinical course, treatment andperinatal outcome of twin pregnancies discordant for intrapericardial teratoma.Following PRISMA and Cochrane guidelines for systematic reviews, we selected allpublications that published on prenatally diagnosed twin pregnancies discordantfor intrapericardial teratoma. Seven publications were found, all of which were casereports and were included in the final analysis, plus a recent case presented in thispublication. To date, 8 cases of twin pregnancies discordant for intrapericardialteratoma have been reported. All (8/8) had severe pericardial effusion, 5 (62.5%)developed hydrops and 2/8 (25%) polyhydramnios. Five (62.5%) cases were treatedwith pericardiocentesis and 2 (25%) underwent concomitant amniodrainage becauseof polyhydramnios. All cases were delivered by cesarean section with a mediangestational age of 34 weeks (RIC 32-35) and all were operated within the first threedays of life. In 7/8 cases (87.5%), the tumors originated in the ascending aorta. Bothtwins survived in all cases. In conclusion, pericardiocentesis (+/- amniodrainage) of theaffected twin is the only fetal therapy reported to date in twin pregnancy discordantfor intrapericardial teratoma and the results are encouraging, although the evidenceis scarce. Prenatal treatment of twin pregnancies presenting with this pathologyshould only be considered in the context of a highly trained multidisciplinary careteam.